Enhancing accounting literacy with Smartaccxel: an interactive excel template - Muhamad Hanafi, Nurfazilahaini; Wan Fauzi, Wan Noor Asmuni; Wan Ahmad, Wan Noraswaniaty; Ariffin, Muhaniza Zainal; Ahmad, Junaidah Hanim; Hassan, Othman Zailani (Faculty of Accountancy, Universiti Teknologi MARA (UiTM) Cawangan Kelantan, 2025)
Accounting is a fundamental skill essential for financial literacy, yet many pre-diploma students without prior accounting knowledge struggle to understand basic concepts, particularly the identification of debit and credit in transactions. Traditional teaching methods often fail to provide real-time feedback, making it difficult for students to recognize and correct their mistakes. To address this challenge, this project introduces SmartAccXcel (Smart Accounting learning with Excel) an innovative Excel-based interactive learning template designed specifically for non-accounting students. SmartAccXcel features an automated feedback system that validates student inputs, a step-by-step account classification guide, and an interactive approach to identifying debit and credit. By integrating these features, SmartAccXcel enhances students' learning experiences, allowing them to self-assess and correct errors instantly, ultimately improving their understanding of fundamental accounting principles. This innovation provides multiple benefits, including self-paced learning, reduced reliance on lecturers, and increased confidence in financial decision-making. Additionally, SmartAccXcel has strong commercialization potential, as it can be integrated into educational institutions, licensed to universities and training centers, or offered as a digital self-learning tool. With its ability to bridge the knowledge gap in accounting education, this project will help simplify accounting concepts for beginners, improve understanding and instil interest towards the accounting subject.